2016
DOI: 10.1136/bmjopen-2016-012210
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in red blood cell transfusion in elective surgery: a post hoc multicentre cohort study

Abstract: ObjectivesA post hoc gender comparison of transfusion-related modifiable risk factors among patients undergoing elective surgery.Settings23 Austrian centres randomly selected and stratified by region and level of care.ParticipantsWe consecutively enrolled in total 6530 patients (3465 women and 3065 men); 1491 underwent coronary artery bypass graft (CABG) surgery, 2570 primary unilateral total hip replacement (THR) and 2469 primary unilateral total knee replacement (TKR).Main outcome measuresPrimary outcome mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…The superiority of RaPN was strengthened in female patients in meta‐regression analysis. Our finding supported that RaPN may reduce overtransfusion in women secondary to liberal transfusion strategy and nonsex specific transfusion threshold …”
Section: Discussionsupporting
confidence: 82%
“…The superiority of RaPN was strengthened in female patients in meta‐regression analysis. Our finding supported that RaPN may reduce overtransfusion in women secondary to liberal transfusion strategy and nonsex specific transfusion threshold …”
Section: Discussionsupporting
confidence: 82%
“…In a recent publication we assumed that this is due to clinicians applying the same absolute transfusion thresholds irrespective of a patient's gender. This, together with the common use of a liberal transfusion strategy despite the recommendations in relevant guidelines, may lead to over-transfusion in women [21]. These findings will be applied to future predictive models in order to further optimize PBM in women.…”
Section: Discussionmentioning
confidence: 99%
“…This sex difference is not completely new. In a large multicenter study enrolling 6530 patients with elective cardiac surgery, hip replacement surgery, and knee replacement surgery, Gombotz et al 23 found higher transfusion rates and volume in women compared with men. The authors concluded that clinicians tend to apply the same absolute transfusion thresholds for both sexes, leading to overtransfusion in female patients.…”
Section: Discussionmentioning
confidence: 99%